Association of hydrazine and SGPT level two hours after drug administration at the end of intensive phase treatment of pulmonary tuberculosis patients - Ave Olivia Rahman; Jarir At Thobari; Mustofa Mustofa (Tropical Medicine Journal, 2012)
ABSTRACTIntroduction: Isoniazid in the regiment treatment of pulmonary tuberculosis patients causes side effects. Hepatotoxicity is one of the isoniazid’s side effects that need medical attention. Isoniazid-induced hepatotoxicity has no correlation with high level of isoniazid in plasma. However, several animal studies show it has an association with hydrazine, a metabolite of isoniazid. The role of hydrazine in isoniazid-induced hepatotoxicity among tuberculosis patients is unclear.Objective: The aim of this study was to analyze the correlation of hydrazine and serum glutamic-pyruvic transaminase (SGPT) levels at two hours after drug administration in the end of intensive phase treatment of pulmonary tuberculosis patients.Methods: This was an observational study with cross-sectional design. Fifty eight newly diagnosed pulmonary tuberculosis patients were enrolled in this study. Venous blood sampling was collected at two hours after drug administration in the end of intensive phase treatment. SGPT level was measured by an automatic chemical analyzer. Hydrazine level was measured by using high-performance liquid chromatography (HPLC). Statistical significance was analyzed using correlation test.Results and Discussion: The incidence of hepatotoxicity was 3.4% and about 8.6% patients had elevated SGPT at two hours after drug administration in the end of intensive phase treatment. There was no correlation between hydrazine level and SGPT levels in this study. These results indicated that hepatotoxicity or minimal liver damage in some patients might occur in the administration of standard dose isoniazid. It might be caused by isoniazid’s metabolites itself, or various other factors.Conclusions: There was no correlation between hydrazine level and SGPT levels at 2 hours after drug administration in the end of intensive phase treatment in this study.